Bone metastases from a 1p/19q codeleted and IDH1-mutant anaplastic oligodendroglioma: a case report - Burgy, Mickaël; Chenard, Marie-Pierre; Noël, Georges; Bourahla, Khalil; Schott, Roland (Journal of medical case reports, 2019)
Background Oligodendroglioma is a rare type of primary brain tumor which, like other malignant gliomas, metastasizes very rarely even when in high-grade form. Case report A 36-year-old white man diagnosed 29 months previously as having 1p/19q codeleted anaplastic oligodendroglioma presented bilateral cruralgia and lower limb motor deficits. A computed tomography scan showed multiple osteoblastic bone lesions. The presence of oligodendroglial cells was revealed by bone marrow biopsy and confirmed by immunohistochemical analyses. A positon emission tomography-computed tomography scan confirmed the exclusive involvement of bones. Conclusion This case joins less than 20 other reported cases of oligodendroglioma bone marrow metastasis, and is one of only a handful of cases of diffuse bone metastases beyond the axial skeleton. To the best of our knowledge, the early relapse of 1p/19q codeleted anaplastic oligodendroglioma with this distribution of metastases has never been described in the literature.